Specific autophagy and ESCRT components participate in the unconventional secretion of CFTR. Issue 10 (3rd October 2018) - Noh, Shin Hye; Gee, Heon Yung; Kim, Yonjung; Piao, He; Kim, Jiyoon; Kang, Chung Min; Lee, Gahyung; Mook-Jung, Inhee; Lee, Yangsin; Cho, Jin Won; Lee, Min Goo
ABSTRACT: The most common mutation in cystic fibrosis patients is a phenylalanine deletion at position 508 (ΔF508) in the CFTR (cystic fibrosis transmembrane conductance regulator) gene. This mutation impairs cell-surface trafficking of CFTR. During cellular stress, core-glycosylated CFTRΔF508 is transported to the cell surface from the endoplasmic reticulum (ER) via an unconventional route that bypasses the Golgi. However, the mechanisms for this unconventional secretory pathway of CFTR are not well delineated. Here, we report that components of the macroautophagy/autophagy and ESCRT (endosomal sorting complex required for transport) pathways are involved in unconventional secretion of CFTR. In mammalian cells, we found that autophagic pathways were modulated by conditions that also stimulate unconventional secretion, namely ER stress and an ER-to-Golgi transport blockade. Additionally, we found that knockdown of early autophagy components, ATG5 and ATG7, and treatment with pharmacological autophagy inhibitors, wortmannin and 3-methyladenine, abolished the unconventional secretion of CFTR that had been stimulated by ER stress and an ER-to-Golgi blockade. Interestingly, immunoelectron microscopy revealed that GORASP2/GRASP55, which mediates unconventional CFTR trafficking, is present in multivesicular bodies (MVB) and autophagosomal structures under ER stress conditions. A custom small-interfering RNA screen of mammalian ESCRT proteins that mediate MVB biogenesis showed that silencing of some ESCRTs, including MVB12B, inhibited unconventional CFTRΔF508 secretion. Furthermore, MVB12B overexpression partially rescued cell-surface expression and Cl − channel function of CFTRΔF508. Taken together, these results suggest that components involved in early autophagosome formation and the ESCRT/MVB pathway play a key role in the stress-induced unconventional secretion of CFTR.